Exfoliation of two-dimensional phosphorene sheets with enhanced photocatalytic activity under simulated sunlight - Pan, Shuihong; He, Jun; Wang, Chengjun; Zuo, Yuegang (Elsevier, 2018)
Two-dimensional phosphorene (2D-BP) nanosheets were successfully prepared by an environmental friendly water exfoliation process. The morphology and structure of exfoliated 2D-BP nanosheets were characterized by SEM, AFM, Raman and UV–Vis. The photocatalytic results demonstrated that 2D-BP nanasheets can generate reactive oxygen species of 1O2 and O2− and effectively enhance the photodegradation of dibutyl phthalate pollutants when coexist with water, oxygen, and light.